A MODEL FOR SELECTION OF DECENTRALIZED SANITARY SEWER SYSTEMS FOR SMALL MUNICIPALITIES - de Souza Batista, Gabriele Souza; Rocha , Elis Gean; Souza, Ayrton Flavio Nascimento de Souza; Ferreira, José Ailton da Costa; Lacerda, Ivens Lorran Clemente de; França , Lorena Rayssa Cunha; Carvalho , Millena Alves; Lacerda, Mateus Clemente de; Cunha , Patricia Herminio (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
The precariousness of sanitation services in small Brazilian municipalities is exacerbated by technical and financial limitations. In these places treatment technologies need to be simple, sustainable, economically viable, and socially accessible. This work aims to propose a selection model for decentralized sewage treatment technologies for small municipalities. The PROMETHEE II multi-criteria method was used to rank the technologies with aid decision-making agents to prioritize technical, environmental, economic, and social criteria based on the characteristics of the sewer basins. After validating the method in the sewage catchment areas of four municipalities in Paraíba, the results showed that the constructed wetlands technology occupied the best position in 88.9% of the sewer basins. This technology stands out for its high organic matter and suspended solids removal efficiency, in addition to not generating sludge and performing well in terms of social criteria (odor production and vectors). The septic tank and septic tank + anaerobic filter alternatives ranked lower in the basins studied. The robustness of the method and the assignment of preferences to criteria for sewer basins with different classifications indicate that the model is replicable for small municipalities. Thus, the study contributes to the optimization of decision-making for sewage treatment systems, allowing the better use of resources, the reduction of vulnerabilities, and promotion of municipal development.